Preserving Family Bonds: Examining a Child’s Right to Family Integrity - Kate Daus (Washington University Journal of Law and Policy, 2025)
This Note examines the holding in Chambers v. Sanders—a 2023 Sixth Circuit decision that held that children do not have a constitutional right to family integrity when a parent is wrongfully incarcerated. Children’s rights and the right to family integrity have changed and developed throughout American history. While the Supreme Court left open the question as to whether children have this right, a majority of circuit courts have recognized a reciprocal right to family integrity shared by parents and children under the Fourteenth Amendment. The Sixth Circuit, however, does not. This Note argues that the Sixth Circuit should have reached the opposite conclusion in Chambers v. Sanders. The Court should recognize a child’s Fourteenth Amendment Due Process right to family association and integrity. Further the Sixth Circuit should reassess related standards that have failed to address harms caused by wrongful state actions.
Keywords: FamilyIntegrityRights; ChildrensRights; FourteenthAmendment